2018
DOI: 10.1002/jib.507
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical study of pinhão flour as source of adjunct in beer production

Abstract: Pinhão seed flour can be used as a soluble adjunct in the production of beer. The objective of this work was to determine the proportion of pinhão flour and barley malt to obtain a suitable extract for beer production. In addition, as a source of starch it is important to determine the viscoamylographic properties and chemical composition. To achieve this, three samples of pinhão flour were manufactured: raw, frozen raw and pre‐gelatinised flour. Of these, pre‐gelatinised pinhão flour was compatible with the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
1
7
0
1
Order By: Relevance
“…Almonds Barreto et al 24 Jorge et al 25 Pigozzi et al 26 Helm et al 23 It was observed that Pinhão flour could be considered a source of total starch, with an average content of 51.28%, where the resistant starch content corresponds to 3.81%. However, the total starch content is lower than that reported in recent studies, which show values of starch present in Pinhão flour between 63.75 and 80.99% (Table 2).…”
Section: Almonds Huskmentioning
confidence: 99%
See 2 more Smart Citations
“…Almonds Barreto et al 24 Jorge et al 25 Pigozzi et al 26 Helm et al 23 It was observed that Pinhão flour could be considered a source of total starch, with an average content of 51.28%, where the resistant starch content corresponds to 3.81%. However, the total starch content is lower than that reported in recent studies, which show values of starch present in Pinhão flour between 63.75 and 80.99% (Table 2).…”
Section: Almonds Huskmentioning
confidence: 99%
“…O. Kuntze is a coniferous plant native to the southern regions of Brazil, northeastern Argentina, and eastern Paraguay 22 . The seed almond corresponds to 74% of its weight 23 Pinhão flour can be considered a good source of starch, presenting between 63.7 and 81.0% of starch and between 5.0 and 6.36% of proteins, 1.0 and 2.2% of lipids, and about 4.7 to 15% of dietary fiber 23‐26 . Some studies have used Pinhão flour or starch as a base for edible films 8,27‐30 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there was an increase in RC, without changing the crystalline patterns, as reported in other studies. [1,33,40,44] However, Singh and Nath [34] evaluated sago starch cross-linked by POCl 3 Values are presented as mean values ± standard deviation. a,b,c,d,e,f,g) The same letters on the same line not differ by Tukey's test (p < 0.05).…”
Section: X-ray Powder Diffractometrymentioning
confidence: 99%
“…The proximal composition of the seed reveals its great nutritional value. In addition to starch, which represents about 64% of its weight, pinhão seed contains approximately 6.4% of protein, 1.0% of lipids, 5.2% of fibers, and 2.5% of ashes (dry basis) …”
Section: Introductionmentioning
confidence: 99%